PENGARUH LINGKUNGAN KERJA DAN KOMITMEN TERHADAP KINERJA KARYAWAN PADA PT ALAMJAYA WIRASENTOSA PEMATANGSIANTAR - Agatha Deo S Batubara (Jurnal of Management and Social Sciences, 2024)
The destinations of this examination are: 1. To portray the workplace, responsibility and execution of representatives at PT Alamjaya Wirasentosa Pematangsiantar. 2. To decide the impact of workplace and obligation to worker execution at PT Alam jaya Wirasen tosa Pematang siantar either all the while or halfway. The exploration configuration utilized is library examination and field research. The populace in this investigation is the whole populace of PT Alamjaya Wirasentosa Pematangsiantar, adding up to 26 individuals. The information utilized are subjective information and quantitative information, and information assortment methods through surveys, meetings and documentation. At that point the information examination procedure utilized the traditional supposition test, subjective distinct investigation and quantitative enlightening examination. The examination results from numerous straight relapse, in particular Ŷ = 1.017 + 1.044X1 + 0.528X2, implying that thhere is a positive impact between workplace and obligation to worker execution. The aftereffects of the connection coefficient examination acquired a worth of R = 0.889, which implies that there is a solid and posiitive connection betwieen workplace and obligation to representative execution. At that point the assurance coefficient esteem = 0.791, implying that the high and low presentation of representatives at PT Alamjaya Wirasentosa Pematangsiantar of 79.1% can be clarified by workplace and responsibility while the leftover 20.09% is impacted by different factors like authoritative culture, correspondence, pay, improvement. profession, administration style, preparing, position fulfillment and different facetors not inspected in this investigation. From the consequences of the preparing an estimation of the survey, the creators presume that the workplace and responsibility applied by PT Alamjaya Wirasentosa Pematangsiantar have a positive and huge impact on representative execution. This is confirmed by synchronous theory testig, where the test outcomes fcount (43.454)> Ftable (3.422) with an importance level of 0.000 <α 0.05.